Analyzing the Impact of Foreign Direct Investment, Money Flow Dynamics, and Inflation on Economic Growth: Evidence from Special Economic Zones - Andriansyah, Andriansyah; Erlina, Erlina; Silalahi, Amlys Syahputra; Sadalia, Isfenti; Ilham, Rico Nur (International Journal of Business, Economics & Financial Studies, 2023)
Establishing robust Special Economic Zones within the determined territorial boundaries of the Republic of Indonesia is crucial for attracting increased investments, fostering industrial growth, and optimizing economic activities with high value, propelling the nation's economic development forward. This study determines the effects of foreign direct investment, velocity of money, and inflation on economic growth in Indonesian Special Economic Zones. This time series approach involves 35 years of data collected from the Central Bureau of Statistics Indonesia. The result indicates that foreign direct investment and money velocity significantly affect economic growth. Besides that, inflation does not affect economic growth. In conclusion, this study has successfully identified the factors influencing economic growth. Also, this study found that inflation does not significantly affect economic growth in Indonesia's Special Economic Zones.